A fragment of the world, a piece of human consciousness: Tim Bowling’s "The Bone Sharps" (2007) and "The Tinsmith" (2012) - Martínez Serrano, Leonor María (Journal of English Studies, 2017)
Canadian novelist, poet and essayist Tim Bowling is one of the most prestigious authors in 21st-century Canadian letters. A prolific and versatile author, he has published twelve poetry collections, four novels, a memoir and a work of creative non-fiction so far. This paper looks at two of his novels, "The Bone Sharps" (2007) and "The Tinsmith" (2012), tools of knowledge that explore not just human consciousness as the lens through which we make sense of reality, including our selves, but also history, memory and identity, epistemology and ethics. A fragment of the world and a piece of human consciousness: this is what both novels are.